Health and education problems of children and youth with disabilities in Latvia - Ušča, Svetlana; Korņiļjevs, Ivans; Ļubkina, Velta (Social Welfare: Interdisciplinary Approach, 2011)
Since Latvia has acceded to the European Union, the issue of equal opportunities of education for all has become topical: the legislation is harmonized, the attitude towards children with special needs is changed in education from segregation and social isolation of disabled persons to integration and inclusion. The authors of the article identify the existing problems related to the health and education of disabled children and youth, explain the terminology existing in the country, analyze statistical data of recent years regarding the number of disabled people and describe the opportunities offered by the country to the target audience of the article on all levels of education.